An Analysis Of The Use Of Technology In English Language Teaching And Learning In Junior High Schools In Merauke - Seli Marlina Radja Leba; Temaja, I Gede Bagus Wisnu Bayu (International Journal of Education, Vocational and Social Science, 2023)
In language teaching and learning, we have a lot to select from the world of technology: Radio, TV, CD-ROM, Computers, CALL, the Internet, Electronic Dictionaries, Email, Blogs and Audio Cassettes, PowerPoint, Videos, DVDs or VCDs. The last two decades have witnessed a revolution due to the onset of technology, and it has changed the undercurrents of various industries. It has also influenced industries and how people interact and work. This rapid growth and expansion of information technology have presented a better pattern for discovering a new teaching model. Technology plays a very vital role in English teaching. Using multimedia to generate a context to teach English has its exclusive advantages. This paper investigated the need for multimedia technology in language teaching and discussed the problems tackled using these technologies. It also intends to make English teachers conscious of the strategies to use it authentically.